Association between plasma kisspeptin levels and adolescent gynecomastia - Mustafa Arif Aluclu; Selcuk Sen; Muazez Cevik (Wolters Kluwer Medknow Publications, 2016)
Background: Gynecomastia is defined as benign proliferation of male breast glandular tissue. To date, the pathophysiology of adolescent gynecomastia (AG) remains unclear. Kisspeptin is a polypeptide that plays an important role in the regulation of the hypothalamic-pituitary-gonadal hormonal axis. In this study, we investigated whether there is a relationship between kisspeptin and AG. Materials and Methods: This study included 40 males between 9 and 18 years of age diagnosed with gynecomastia. The control group consisted of 30 young healthy males in the same age range. The participants were evaluated with respect to anthropometric measurements (age, height, body weight, body mass index, breast and pubic stages and testicular volume). The levels of kisspeptin, follicle-stimulating hormone, luteinizing hormone, estradiol (E2), testosterone (T), and ratio of E2 to T were measured in both groups. Results: The mean age was 13.8 years. There were no differences between the groups in terms of anthropometric parameters, plasma gonadotropin levels, estrogen levels, and E2/T (P > 0.05). Plasma kisspeptin (0.77 and 0.54 ng/mL, P < 0.05) and T (253.9 ng/dL and 117.9 ng/dL) levels were significantly higher in the AG group than in the control group (P < 0.001). Conclusion: Kisspeptin levels are an important factor in AG.